152k views
2 votes
Use foil (a + 3)(a - 2)

2 Answers

3 votes

Answer:


(a+3)(a-2)=a^2+a-6

Explanation:

The given expression is:


(a+3)(a-2)

Using FOIL, we multiply the;

First terms:
a* a=a^2

Outside terms:
a* -2=-2a

Inner terms:
3* a=3a

Last terms:
3* -2=-6

Putting all together we have:


(a+3)(a-2)=a^2-2a+3a-6

This simplifies to
(a+3)(a-2)=a^2+a-6

User Michel Sabchuk
by
6.2k points
6 votes

Answer:


\left(a+3\right)\left(a-2\right)=a^2+a-6=

Explanation:

Given expression is
\left(a+3\right)\left(a-2\right).

Now we need to multiply this using FOIL.

F = First
=\left(a\right)\left(a\right)= a^2

O = Outside
=\left(a\right)\left(-2\right)= -2a

I = Inside
=\left(3\right)\left(a\right)= 3a

L = Last
=\left(3\right)\left(-2\right)= -6

Hence we get :


\left(a+3\right)\left(a-2\right)=a^2-2a+3a-6=a^2+a-6=

User SLLegendre
by
5.8k points